Aerosolization of viable Mycobacterium tuberculosis bacilli by tuberculosis clinic attendees independent of sputum-Xpert Ultra status - Patterson, Benjamin; Dinkele, Ryan; Gessner, Sophia; Koch, Anastasia; Hoosen, Zeenat; January, Vanessa; Leonard, Bryan; McKerry, Andrea; Seldon, Ronnett; Vazi, Andiswa; Hermans, Sabine; Cobelens, Frank; et al. (Proceedings of the National Academy of Sciences - PNAS, 2024)
Potential ( ) transmission during different pulmonary tuberculosis (TB) disease states is poorly understood. We quantified viable aerosolized from TB clinic attendees following diagnosis and through six months' follow-up thereafter. Presumptive TB patients (n=102) were classified by laboratory, radiological, and clinical features into Group A: Sputum-Xpert Ultra-positive TB (n=52), Group B: Sputum-Xpert Ultra-negative TB (n=20), or Group C: TB undiagnosed (n=30). All groups were assessed for bioaerosol release at baseline, and subsequently at 2 wk, 2 mo, and 6 mo. Groups A and B were notified to the national TB program and received standard anti-TB chemotherapy; was isolated from 92% and 90% at presentation, 87% and 74% at 2 wk, 54% and 44% at 2 mo and 32% and 20% at 6 mo, respectively. Surprisingly, similar numbers were detected in Group C not initiating TB treatment: 93%, 70%, 48% and 22% at the same timepoints. A temporal association was observed between bioaerosol release and TB symptoms in all three groups. Persistence of bioaerosol positivity was observed in ~30% of participants irrespective of TB chemotherapy. Captured bacilli were predominantly acid-fast stain-negative and poorly culturable; however, three bioaerosol samples yielded sufficient biomass following culture for whole-genome sequencing, revealing two different lineages. Detection of viable aerosolized in clinic attendees, independent of TB diagnosis, suggests that unidentified transmitters might contribute a significant attributable proportion of community exposure. Additional longitudinal studies with sputum culture-positive and -negative control participants are required to investigate this possibility.